Disparitas Hukum Pidana Terhadap Pelaku Kekerasan Seksual Pada Anak - Rahmawati, Rahmawati; Hartiwiningsih, Hartiwiningsih; Rustamaji, Muhammad; Sulistiyanta, Sulistiyanta; Abdillah, Muhammad (AL-ISTINBATH : Jurnal Hukum Islam, 2023)
This research aims to elucidate how criminal law disparities against perpetrators of sexual violence against children manifest based on Islamic law in Indonesia. The legal disparities indicate that child victims of sexual violence have not received comprehensive legal justice. This study adopts a qualitative descriptive approach, collecting data through exploration and reading online media with the keywords 'sexual violence against children in Indonesia' on the Google search engine. This paper reveals that legal imbalances have undermined the value of justice for child victims of sexual crimes, affecting them both psychologically and physically, and leading to other consequences such as dropping out of school, forced marriage to the perpetrator, and suicide. This study is crucial to bring about justice based on Islamic law for child victims of sexual crimes, juxtaposed with Pancasila justice. It highlights that the criminal legal disparities in cases of sexual violence consistently place children as the disadvantaged objects of legal justice. True legal inequality would not occur if the application of the law is based on Islamic Law grounded in divine values, as the punishment for perpetrators of sexual violence in Islam can be judged as hudud crimes, qhisas crimes, and ta'zir crimes.